A 125-base-pair CEN6 DNA fragment is sufficient for complete meiotic and mitotic centromere functions in Saccharomyces cerevisiae. - Cottarel, G (1989)
Saccharomyces cerevisiae centromeres contain a conserved region ranging from 111 to 119 base pairs (bp) in length, which is characterized by the three conserved DNA elements CDEI, CDEII, and CDEIII. We isolated a 125-bp CEN6 DNA fragment (named ML CEN6) containing only these conserved elements and assayed it completely separated from its chromosomal context on circular minichromosomes and on a large linear chromosome fragment. The results show that this 125-bp CEN6 DNA fragment is by itself sufficient for complete mitotic and meiotic centromere functions.